Corrosion Studies on HVOF Sprayed Ni-20Cr and Ni-50Cr Coatings on ASTM A213 TP347H Boiler Steel at 700 degree Celsius - T.S Bedi; S. S Aulakh; G. Kaushal (Asian Review of Mechanical Engineering, 2013)
Ni-20Cr and Ni-50Cr coatings were deposited on ASTM A213 TP347H boiler tube steel by High Velocity Oxy Fuel (HVOF) thermal spray process. High temperature corrosion studies were conducted to investigate the comparative performance of the coatings. The tests were conducted in a simulated boiler environment (Na2SO4–60%V2O5) at 7000C for 50 cycles. Each cycle consisted 1 hour of heating in the silicon carbide tube furnace followed by 20 min of cooling in air. The weight change measurements were recorded after each cycle to establish the kinetics of high temperature corrosion. The corroded samples were characterized by SEM/EDS analysis. It was observed that Ni-50Cr coated specimen was found to be more protective than Ni-20Cr coated specimen.